Emotional intelligence in gifted students. (May 2017) - Zeidner, Moshe; Matthews, Gerald
This article aims at shedding light on the emotional intelligence (EI) of gifted and high ability students. We begin by presenting a brief overview of EI theory and research and its relevance to gifted education. We then present theoretical considerations bearing on the nature of the relationship between cognitive and EI. This is followed by a survey of correlational and individual difference research bearing on the EI-high ability nexus. We then move on to present a number of general guidelines for the development of an EI training program designed to foster emotional and social competencies in gifted students. We conclude by offering some broad generalizations about EI in gifted students and point out the areas of needed future research.